Power and Communication in Digital Society - Núñez Ladevéze, Luis (2011)
The growing role of information in the digital society has reopened the debate on the relationship between political power and communication, and intensifies the concern about social and political influences of the media and the privileges of the rulers through various mechanisms to control the information. The key is to distinguish the information from the communications of the entertainment typically of cultural industry and get back on traditional values to establish criteria for both freedom of expression intrinsic to information as to demand the minimum quality of the content of communication to the entertainment.